Interdisciplinaridade na horta escolar: processo ensino/aprendizagem - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Environmental education needs to be inserted in schools system in doing so It is necessary to rethink the curricular proposals for pedagogical action that assures continuous trajectory of lifelong learning to the students. The Elementary School Aderbal Tapajos Caetano Corrêa, made possible the interdisciplinary insertion working with School Vegetable Garden project that involved teachers in the classroom, pedagogical support to use the garden as a laboratory. However, Mais Educação Program that belongs to Federal Government was responsible to motivate the insertion of School Vegetable Garden (SVG) in the education routine, and when the program ended, it was necessary for the school to continue this kind of working, arousing the interest of public and private institutions. The Interministerial Ordinance no. 1.010/2006 establishes guidelines to the "Promotion of Healthy Food in public and private schools networks", expanding to national curricular parameters (PCNs in Portuguese). The National School Feeding Program (PNAE) has the management of school feeding and the School Feeding Council establishes an nutritionists work at schools. The contributors participation was importance for the accomplishment of the work in SVG, as well as the teachers from 5 year of Elementary School in providing interdisciplinary to the students and integrating different subjects during the applications of SVG in its routine. This research aimed to promote educational actions that influence the interdisciplinary in SVG and to integrate curricular contents into meaningful and innovative active approaches in the teaching / learning process. Interdisciplinary and curricula advice aimed the cognitive and physical developing, interactive and affective skills, health, quality of life and respect for the environment. Bibliographic and field works were the main feature of this research. It was adopted the qualitative approach and significant, innovative and active method.
Keywords: Currículo; Interdisciplinaridade; Horta escolar; CNPQ:: CIÊNCIAS BIOLÓGICAS